Beyond Behavioral Inhibition: A Computer Avatar Task Designed to Assess Behavioral Inhibition Extends to Harm Avoidance - Allen, Michael Todd; Jameson, Molly M.; Myers, Catherine E. (Frontiers in Psychology, 2017)
Personality factors such as behavioral inhibition (BI), a temperamental tendency for avoidance in the face of unfamiliar situations, have been identified as risk factors for anxiety disorders. Personality factors are generally identified through self-report inventories. However, this tendency to avoid may affect the accuracy of these self-report inventories. Previously, a computer based task was developed in which the participant guides an on‐screen “avatar” through a series of onscreen events; performance on the task could accurately predict participants’ BI, measured by a standard paper and pencil questionnaire (Adult Measure of Behavioural Inhibition, or AMBI). Here, we sought to replicate this finding as well as compare performance on the avatar task to another measure related to BI, the harm avoidance scale of the Tridimensional Personality Questionnaire (TPQ). The TPQ includes harm avoidance scales as well as scales assessing reward dependence, novelty seeking and persistence. One hundred and one undergraduates voluntarily completed the avatar task and the paper and pencil inventories in a counter-balanced order. Scores on the avatar task were strongly correlated with BI assessed via the AMBI questionnaire, which replicates prior findings. Females exhibited higher HA scores than males, but did not differ on scores on the avatar task. There was a strong positive relationship between scores on the avatar task and harm avoidance scores. One aspect of HA, fear of uncertainty was found to moderately mediate the relationship between AMBI scores and avatar scores. Novelty seeking had a strong negative relationship with scores on the avatar task, but there was no significant relationship between reward dependence and scores on the avatar task. These findings indicate the effectiveness of the avatar task as a behavioral alternative to self-report measures to assess avoidance. In addition, computer based behavioral tasks are a viable alternative to paper and pencil self-report inventories, particularly when assessing anxiety and avoidance.